Respostas

2013-11-09T15:43:20-02:00
A) x² + 7x + 10 = 0

Δ = b² - 4ac
Δ = 7² - 4 . 1 . 10
Δ = 49 - 40
Δ = 9 
(√9 = 3)

b) x² - 8x + 12 = 0

Δ = b² - 4ac
Δ = (-8)² - 4 . 1 . 12
Δ = 64 - 48
Δ = 16
(√16 = 4)

c) x² + 2x - 15

Δ = b² - 4ac
Δ = 2² - 4 . 1 . (-15)
Δ = 4 + 60
Δ = 64
(√64 = 8)


2013-11-09T15:44:55-02:00
A)
Δ = b² -4ac
Δ = (-7)² -4 *1 * 10
Δ = 49 -40Δ = 9
x' = (-b + √∆)/ 2a
(-(-7) + 3)/2 * 1
(7 + 3)/2
10/2= 5
x'' = (-b - √∆)/ 2a
(-(-7) - 3)/2 * 1
(7 - 3)/2
4/2= 2

b)
Δ = b² -4ac
Δ = (-8)² -4 *1 * 12
Δ = 64 -48Δ = 16
x' = (-b + √∆)/ 2a
(-(-8) + 4)/2 * 1
(8 + 4)/2
12/2= 6
x'' = (-b - √∆)/ 2a
(-(-8) - 4)/2 * 1
(8 - 4)/2
4/2= 2

c)
Δ = b² -4ac
Δ = 2² -4 *1 * (-15)
Δ = 4 + 60Δ = 64
x' = (-b + √∆)/ 2a
(-2 + 8)/2 * 1
(-2 + 8)/2
6/2= 3
x'' = (-b - √∆)/ 2a
(-2 - 8)/2 * 1
(-2 - 8)/2
-10/2= -5